MODEL OF SUPERVISION OF THE IMPLEMENTATION OF CONSTITUTIONAL RIGHTS TO ENSURE THE PROTECTION AND WELFARE OF DOMESTIC WORKERS IN THE ADMINISTRATIVE CITY OF EAST JAKARTA: MODEL PENGAWASAN IMPLEMENTASI HAK KONSTITUSIONAL UNTUK MENJAMIN PERLINDUNGAN DAN KESEJAHTERAAN PEKERJA RUMAH TANGGA DI KOTA ADMINISTRATIF JAKARTA TIMUR - Fakhris Lutfianto Hapsoro; Khilmatin Maulidah; Fikrotul Jadidah; Ade Lita; Muhammad Wendra; Muhammad Ragil Wicaksono; Supriyanto (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This study aims to analyze the legal protection of domestic workers (PRT) within the framework of constitutional and statutory law, identify the factors contributing to weak supervision over the fulfillment of domestic workers' rights in the household sector, and formulate an effective supervision model within the administrative context of East Jakarta. Employing a normative-empirical legal method with statutory, conceptual, and sociological approaches, this research integrates primary data obtained through interviews and Focus Group Discussions (FGDs) involving government institutions and civil society organizations. The findings reveal that constitutional protection for domestic workers is guaranteed under Article 27(2) and Article 28D(2) of the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945). Nevertheless, implementation remains weak due to the absence of legal recognition of households as workplaces within the national labor law framework. The ineffectiveness of supervision in fulfilling domestic workers' rights is attributed to four key factors: limited scope of supervision, restricted jurisdiction and authority of local government agencies at the administrative city level, institutional fragmentation among state bodies, and a formalistic bureaucratic culture. As a solution, this study proposes an effective supervision model grounded in the principles of legal inclusivity, institutional collaboration, and community participation. The model consists of five main components: (1) neighborhood-based registration (RT/RW) to ensure that domestic employment relationships are officially recorded and monitored by the state; (2) strengthening the role of Domestic Worker Placement Agencies (LPPRT) as legal entities responsible for training and grievance mechanisms; (3) integration of cross-agency complaint systems through proactive technology-based coordination; (4) public education and empowerment of domestic worker communities to enhance legal awareness; and (5) establishment of complaint centers at the sub-district (kecamatan) level. This study concludes that labor law reform should aim to recognize domestic work as a legitimate form of employment, decentralize supervisory authority, and develop a living legal system rooted in the values of social justice.